The Transformation of the Surau’s Function in Minangkabau as a Traditional Malay Educational Institution in the Modern Era - Nur ‘Azizah Kallabe; Nyayu Soraya; Baldi Anggara (FKIP - Universitas Riau, 2026)
This study examines the transformation of the surau as a traditional Minangkabau educational institution, tracing its historical roles and its contemporary functions. Historically, the surau served as a multifunctional center for religious instruction, cultural transmission, social interaction, and character formation for young men. It played a significant role in teaching the Qur’an, Hadith, Minangkabau customs, and martial arts, while also functioning as a communal space and temporary residence. However, modernization, the development of formal education, and broader socio-cultural changes have contributed to the decline of these traditional functions. Using a qualitative library research method, this study analyzes historical, ethnographic, and sociological sources to explore the internal and external factors driving this transformation. The findings indicate that institutional reforms, colonial influences, Islamic modernist movements, and evolving community needs have reshaped the surau into a more limited space focused primarily on worship and basic Qur’anic instruction. Nevertheless, the surau remains essential for cultural preservation and character education. This study emphasizes the need to revitalize the surau by integrating traditional values with modern educational demands to strengthen cultural identity and social resilience in the contemporary era.